2010
DOI: 10.3844/jcssp.2010.904.911
|View full text |Cite
|
Sign up to set email alerts
|

Adaptable User Interface Based on the Ecological Interface Design Concept for Multiple Robots Operating Works with Uncertainty

Abstract: Problem statement: When supervising a team of semi-autonomous robots, the operator's task is not only the manipulation of each robot but also achievement of the top goal that is assigned to the entire team of humans and robots. The operators are demanded to comprehend highly complex states and make appropriate decisions in dynamic environment using the limited cognitive resources. The Ecological Interface Design (EID) is a design approach based on visualization of constraints in study environment onto the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The first approach, used by Furukawa (2010), completely implemented again and improved, has enables us to judge to the effectiveness of that proposed. The scaling and comparisons done with rules discovered by ethologists at ants made it possible to show the consistency of found rules.…”
Section: Resultsmentioning
confidence: 99%
“…The first approach, used by Furukawa (2010), completely implemented again and improved, has enables us to judge to the effectiveness of that proposed. The scaling and comparisons done with rules discovered by ethologists at ants made it possible to show the consistency of found rules.…”
Section: Resultsmentioning
confidence: 99%
“…The error signal e (n) is defined as the difference between the primary signal d (n) and the filter output y(n), that is Eq. 12 and 13, (Furukawa, 2010):…”
Section: Methodology Of Adaptive Filtermentioning
confidence: 99%
“…The publication in (Alfred, 2010) summarized the relational data using semi-supervised genetic algorithm-based clustering techniques. The study in (Furukawa, 2010) presented an adaptable user interface which is based on the ecological interface design concept for multiple robots operating with uncertainty. The study in (Mohammed et al, 2010) aimed at presenting principal attacks classifications, especially the study of classification towards evaluation for which suggested some improvements that may allow the generation of test cases selection about attacks by using the classification tree method.…”
Section: Introductionmentioning
confidence: 99%